Clinical Practice Guidelines for theManagement of Hypertension in the Community A Statement by the American Society of Hypertension and the International Society of Hypertension - Weber, Michael A. (2014)
STATEMENTOF PURPOSE: These guidelines have been written to provide a straightforward approach to managing hypertension in the community. We have intended that this brief curriculum and set of recommendations be useful not only for primary care physicians and medical students, but for all professionals who work as hands-on practitioners. We are aware that there is a great variability in access to medical care among communities. Even in so-called wealthy countries, there are sizable communities in which economic, logistic, and geographic issues put constraints on medical care. And, at the same time, we are been reminded that even in countries with highly limited resources, medical leaders have assigned the highest priority to supporting their colleagues in confronting the growing toll of devastating strokes, cardiovascular events, and kidney failure caused by hypertension. Our goal has been to give sufficient information to enable healthcare practitioners, wherever they are located, to provide professional care for people with hypertension. All the same, we recognize that it will often not be possible to carry out all of our suggestions for clinical evaluation, tests, and therapies. Indeed, there are situations in which the most simple and empirical care for hypertension-simply distributing whatever antihypertensive drugs might be available to people with high blood pressure-is better than doing nothing at all. We hope that we have allowed sufficient flexibility in this statement to enable responsible clinicians to devise workable plans for providing the best possible care of hypertension in their communities. We have divided this brief document into the following sections: 1. General introduction, 2. Epidemiology, 3. Special issues with black patients (African ancestry), 4. How is hypertension defined?, 5. How is hypertension classified?, 6. Causes of hypertension, 7. Making the diagnosis of hypertension, 8. Evaluating the patient, 9. Physical examination, 10. Tests, 11. Goals of treating hypertension, 12. Nonpharmacologic treatment of hypertension, 13. Drug treatment of hypertension, 14. Brief comments on drug classes, 15. Treatment-resistant hypertension.